2007
DOI: 10.1553/cia147s52
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MERCATOR data - Part II: variable A & F stars

Abstract: The results of a frequency analysis of photometric observations of variable A and F stars obtained with the mercator telescope are presented. Already 15 γ Dor stars, including a new one, and 3 δ Scuti stars were analysed in detail. A re-analysis of hipparcos data of these stars was done, as well as a comparison with frequencies found in the literature. Light curve parameters (frequencies, amplitudes and phases) were calculated for the variations in the 7 filters of the Geneva photometric system. The amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In previous analyses of the Mercator data (De Ridder et al 2004;Cuypers et al 2006) only two frequencies were found, but now the three frequencies, as given by Henry et al (2005), could be confirmed without any doubt. The threefrequency solution is also clearly present in the Hipparcos data of this star.…”
Section: Hd 2842 = Hip 2510mentioning
confidence: 78%
“…In previous analyses of the Mercator data (De Ridder et al 2004;Cuypers et al 2006) only two frequencies were found, but now the three frequencies, as given by Henry et al (2005), could be confirmed without any doubt. The threefrequency solution is also clearly present in the Hipparcos data of this star.…”
Section: Hd 2842 = Hip 2510mentioning
confidence: 78%